Pengembangan Instrumen Tes pada Materi Polinomial untuk Meningkatkan Kemampuan Berfikir Reflektif Matematis Siswa MA - Izzatunnisai, Rega; Yuhana, Yuyu (Jurnal Riset Pembelajaran Matematika, 2024)
The ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model aims to create a polynomial material test instrument that can improve the mathematical reflective thinking abilities of Madrasah Aliyah (MA) students. Development begins with an analysis stage to determine learning needs and objectives. At the design stage, Protoype-1 was created which included various aspects of the assessment. Protoype-1 was tested on 30 class XI MIPA students at the implementation stage. The results of the instrument reliability analysis show a coefficient of 0.47 which is sufficient for the initial stage of development. The results of this research show that the test instrument created can differentiate students who have different levels of mathematical reflective thinking ability. The questions are of medium difficulty level from 1 to 5, which ensures that the questions are neither too easy nor too difficult for students. In addition, the discriminating power of the five questions tested was of a good level, indicating that the questions were effective in differentiating between students of different levels. The research results show that the test instrument created can be used as a valid and reliable measuring tool to assess MA students' mathematical reflective thinking abilities. Therefore, this instrument can help teachers develop and develop students' mathematical reflective thinking abilities more effectively.